Metallurgy for the non-metallurgist - Reardon, Arthur C (ASM International, 2011)
The completely revised Second Edition of Metallurgy for the Non-Metallurgist provides a solid understanding of the basic principles and current practices of metallurgy. This major new edition is for anyone who uses, makes, buys or tests metal products. For both beginners and others seeking a basic refresher, the new Second Edition of the popular Metallurgy for the Non-Metallurgist gives an all-new modern view on the basic principles and practices of metallurgy. This new edition is extensively updated with broader coverage of topics, new and improved illustrations, and more explanation of basic concepts. Why are cast irons so suitable for casting? Do some nonferrous alloys respond to heat treatment like steels? Why is corrosion so pernicious? These are questions that can be answered in this updated reference with many new illustrations, examples, descriptions of basic metallurgy. This new edition is a must-have ready reference on metallurgy!